Spiritual Trust in AI Systems: Investigating the Role of Ta‘abbud in Personalized E-Commerce for Generation Z - Syahraeni; Syaparuddin; Sitti Nikmah Marzuki; Hukmiah; Sabbar Dahham Sabbar (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
The rapid growth of AI-based e-commerce has yet to integrate spiritual values such as ta‘abbud, essential for Muslim consumers in fostering trust and holistic well-being. This study aims to explore the role of ta‘abbud in AI recommendation systems, enhancing consumer well-being materially and spiritually through increased consumer trust. The research is grounded in four theoretical frameworks: the Technology Acceptance Model (TAM), Consumer Well-Being, Consumer Behavior, and AI Personalization. The study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess relationships between variables. Data were collected via a stratified sampling questionnaire involving 240 Generation Z respondents. The findings reveal that information accessibility significantly influences the shopping experience (R² = 0.743), whereas recommendation quality moderately affects consumer trust (R² = 0.724). Furthermore, AI-based recommendation personalization enhances consumer well-being (R² = 0.635) by improving trust and recommendation relevance (R² = 0.586). Although the effect of ta‘abbud is relatively small, it plays a meaningful role in shaping trust in AI systems, particularly for halal product purchases. This study offers practical implications for Sharia-compliant e-commerce in building consumer loyalty through value-based strategies.